Electrochemical determination of iodine in iodized salt using cetyltrimethylammonium bromide as ion pairing at bare and electrochemically reduced graphene oxide electrodes - Jamilan, Mohd. Azerulazree (2019)
In Sabah and Sarawak states of Malaysia, the use of iodized salt (20–40 mg/kg) is mandatory due to the history of insufficient of iodine content in school children and pregnant woman. Portable method has been developed for a continuous monitoring of Universal Salt Iodization (USI) program. In Malaysia, there was no reported iodine kit or detector using electrochemical approaches for iodized salt. The use of electrochemical method for iodine detection would shorten the analysis time and simplify the overall procedure. In this study, cetyltrimethylammonium bromide (CTAB) has been used in a solution media of samples as ion-pairing for the determination of iodide in iodized salt. Under optimized parameters, a mixture of iodide and CTAB ([CTA]+ I-) was preconcentrated on the working electrode at applied potential of 1.0 V for 60 s causing the I- from [CTA]+ I- oxidized to I2, then immediately produced I2Cl- and reformed an ion-pair with CTA+ as [CTA]+ I2Cl-. The adsorbed ion-pair compounds were reduced after an adsorptive linear sweep voltammetry (AdLSV) scan was applied from 1.0 V–0.2 V at scan rate of 0.1 V/s. Two type of electrodes namely screen-printed carbon electrode (SPCE) and electrochemically reduced graphene oxide modified SPCE (ERGO/SPCE) were used. Based on the cathodic peak produced in AdLSV scan with SPCE, the observed linearity of iodide concentration was in the range of 0.50–4.00 mg/L (sensitivity of 1.38 μA(mg/L)-1, R2=0.9950), limit of detection (LOD) of 0.30 mg/L and limit of quantification (LOQ) of 1.00 mg/L. For ERGO/SPCE, the linearity of iodide concentration of 0.20–1.00 mg/L (sensitivity of 5.05 μA(mg/L)-1, R2=0.9674), LOD of 0.11 mg/L and LOQ of 0.34 mg/L were obtained. The present study was also compared with polarography method and good agreement between SPCE and ERGO/SPCE were observed. For recovery study with known amount of iodide spiked in the sample, SPCE recovered in the range of 100.9%–102.1%, whereas ERGO/SPCE recovered from 96.0%–104.0%. The availability of the optimized technique could provide a future portable device that can be used by the authority for salt iodization monitoring.